Insulinska rezistenca pri bolnicah s sindromom policističnih ovarijev - Merc, Matjaž (Medicinski razgledi, 2009)
Polycystic ovary syndrome (PCOS) is the most common endocrine disease in fertile women. It is also dosely associated with insulin resistance (IR). The purpose of this trial was to investigate the value of dinical and laboratory IR markers routinely used in type 2 diabetes patients (DM2) for the diagnosis of IR in PCOS patients. The goal was to identify the most suitable marker for this condition out of the entire tested panel, which was comprised of ROMAm, intact proinsulin (IP), Sib index and IRIS II score. A total of 50 women with PCOS were recruited, along with 20 comparable, healthy women for the control group. HOMAIR values indicating IR (> 2) were seen in 26 patients (52 %). Patients with IR (based on HOMA'R) had significantly higher values for EMI (p <0.001), fasting glucose (4.7 0.6 vs. 4.2 0.3 nimo1!l, p = 0.001), insulin (16.8 6.2 vs. 7.1 2.1 jJU/ml, p<O.OOl), IP (3.2 2.0vs. 1.8 1.0pmo1!l, p = 0.004), triglycerides (1.16 0.77 vs. 0.80 0.35 mmol/l, p = 0.04), Sib index (6.65 2.61 vs. 22.07 11.36, P < 0.001) and IRIS II score (24 19 vs. 11 11, P = 0.008). A comparison between the control group and PCOS patients with IR and IS showed significant differences in EMI (p<O.OOl), triglycerides (p = 0.048), HDL (p<O.OOl), fasting glucose (p = 0.004), insulin(p<O.OO1), IP (p = 0.001), HOMA'R (p<O.OOl), IRIS II score (p = 0.003) and Sib index (p<O.OOl). The results ofthis study indicate that our patients with PCOS did not reach alevel of IR that would result in higher IP secretion instead of insulin secretion. Out of the entire tested panel, HOMA1R score andSib appeared to be the most suitable markers to assess IR in our patient population. IRIS II score was less sensitive than HOMAđR or Sib. None of the patients reached the required IRIS II threshold in DM2 for IR either. Therefore, HOMAđR and Sib may be suitable indexes for the diagnosis and therapeutic monitoring of IR in this specific patient population.
Keywords: Holesterol; Polycystic Ovary Syndrome; Policistični jajčnik, sindrom; Insulin Resistance; Lipoproteini, LDL, holesterol; Glucose Tolerance Test; Glukoza, tolerančni test; Cholesterol; Lipoproteins, Ldl Cholesterol; Insulinska rezistenca; Krvni sladkor; Lipoproteins, Hdl Cholesterol; Triglycerides; Telesna teža; Lipoproteini, HDL, holesterol; Insulin; Blood; Trigliceridi; Blood Glucose; Inzulin; Body Weight; sindrom policističnih jajčnikov; diagnostika; metode